2013
DOI: 10.1614/wt-d-13-00007.1
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Application Timings Affect Dallisgrass (Paspalum dilatatum) Control in Tall Fescue

Abstract: Field research was conducted in 2010 and 2011 to investigate the efficacy of herbicides for dallisgrass control when applied at various growing (GDD) or cooling degree day (CDD) –based application timings. Herbicide treatments included fluazifop-p-butyl (fluazifop; 105 g ai ha−1), mesotrione (280 g ai ha−1), tembotrione (92 g ai ha−1), topramezone (37 g ai ha−1), and tank mixtures of fluazifop plus mesotrione, tembotrione, or topramezone. Herbicide treatments were applied at either 75, 175, 375, 775 GDD, or 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 37 publications
(46 reference statements)
2
17
0
Order By: Relevance
“…Peak suppression of ultradwarf hybrid bermudagrass clipping yield after TE application was similar to that of PH on Tif Eagle in Mississippi and Champion in North previous GDD studies with C 4 plants (Cross and Zuber, 1972;Elmore et al, 2013). Research predicting the base temperatures of warm-season turfgrasses has been limited to that of Unruh et al (1996), who reported that base temperatures ranged from −0.1 to 12.3°C across warm-season turfgrass species.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Peak suppression of ultradwarf hybrid bermudagrass clipping yield after TE application was similar to that of PH on Tif Eagle in Mississippi and Champion in North previous GDD studies with C 4 plants (Cross and Zuber, 1972;Elmore et al, 2013). Research predicting the base temperatures of warm-season turfgrasses has been limited to that of Unruh et al (1996), who reported that base temperatures ranged from −0.1 to 12.3°C across warm-season turfgrass species.…”
Section: Resultssupporting
confidence: 63%
“…Consecutive daily GDD values were then added to calculate cumulative GDD. The base temperature of 10°C was selected as that is the temperature where photosynthesis becomes minimal for C 4 plants (Berry and Björkman, 1980; McMaster and Wilhelm, 1997) and has been used as the base temperature in previous GDD studies with C 4 plants (Cross and Zuber, 1972; Elmore et al, 2013). Research predicting the base temperatures of warm‐season turfgrasses has been limited to that of Unruh et al (1996), who reported that base temperatures ranged from −0.1 to 12.3°C across warm‐season turfgrass species.…”
Section: Methodsmentioning
confidence: 99%
“…Effective fall herbicide timings for dallisgrass control may be environmentally dependent; changing both spatially and temporally. Future research with TFH applications for dallisgrass control should incorporate the accumulation of cooling degree days similar to Elmore et al (2013) to further increase herbicide efficiency and long-term control.…”
Section: Resultsmentioning
confidence: 99%
“…Dallisgrass is often considered a desirable grass species in pastures and roadsides; however, its wide adaptability to different environmental conditions has likely contributed to it becoming a weed in turfgrass settings. The presence of dallisgrass reduces turfgrass aesthetics and functionality of recreational, commercial, and residential turfgrass stands (Elmore et al, 2013;Henry et al, 2007a). Tolerance of dallisgrass to low mowing heights (1.3 cm) has been reported, suggesting that it can be problematic in both golf course fairways and roughs (Henry et al, 2007a).…”
mentioning
confidence: 99%
“…Previous research investigating the control of warm-season perennials bermudagrass and dallisgrass (Paspalum dilatatum Poir.) demonstrated that late-summer herbicide applications are the most effective seasonal application timing (Brosnan et al 2011;Elmore et al 2013).…”
mentioning
confidence: 99%